ISOLATION OF SALMONELLA GAMINARA - VARELA, GERARDO; OLARTE, JORGE (Laboratorio de Estudios Médicos y Biológicos, CD MEXICO, DF, MEX, 1943)
This thesis arises from the examination of stools from 1,101 children with illnesses involving diarrhea, patients in the children's clinic of Mexico City World-wide distribution records of the occurrence of Salmonella are reviewed Cul- tural and serol
CIENC MEX
Keywords: ISOLATION, SALMONELLA, GAMINARA; CIENCIAS MEDICAS; MEDICINA INTERNA; ENFERMEDADES INFECCIOSAS